Presuposisi dalam Tindak Tutur Ilokusi Melarang di Desa Ngoro, Kecamatan Ngoro, Kabupaten Mojokerto - Dina Aryu Nur Islami; Danang Wijoyanto (Simpati, 2024)
According to Yule in (Pragmatics, 2006:43) presupposition is the speaker's assumption before speaking to the person he is speaking to as an action that produces speech. The aim of this research is how presuppositions in illocutionary speech acts prohibit based on the procedures in the area studied. The theory used in this research is Yule's presupposition theory and is supported by Leech's pragmatic semantic theory. The method used is communication ethnography. Data collection was carried out using the bush and talk method. The data that has been collected is then processed using categorical, descriptive and distributional methods. In this study, the types of speakers were based on age, namely children, teenagers and adults. This research also uses six types of presuppositions. The way to speak when forbidding is based on sound, namely in a soft voice, low voice and loud voice. Apart from that, the prohibition procedure can also be based on its form. Based on the form, there are forms with words, without words and mixed. Then when the speech is delivered it is also explained according to the situation. There are two situations, the situation of oneself and the situation of many people.